Clinical Profile of Pregnant Women with COVID-19 Hospitalized in Regional Referral Hospital : Profil Ibu Hamil dengan COVID-19 yang Dirawat di Rumah Sakit Rujukan - Juminten Saimin; Steven Ridwan; Irawaty Irawaty; Arimaswati Arimaswati; Sadly Salman; Wawan Hermawan (Indonesian Journal of Obstetrics and Gynecology, 2021)
Objective: To determine the clinical profile of pregnant women with COVID-19 who hospitalized in a referral hospital.Methods: This was a descriptive study conducted on pregnant women with COVID-19 who were hospitalized at Regional Hospital of Bau-Bau and Bahteramas Hospital in Southeast Sulawesi from May to July 2020. The confirmation of COVID-19 was based on RT-PCR. Data including characteristics, clinical profile, laboratory test, imaging, management, and outcomes.Results: There were 41 pregnant women with COVID-19 and no maternal death cases. Maternal age was approximately 19 to 39 years, had middle education levels, and was a housewife. Most of them did not know their closed contacts, had no comorbidities, and referrals from other hospitals. They were 3rd-trimester and hospitalized with complaints related to pregnancy. Only 3 cases had complaints related to COVID-19, namely fever and cough. The majority of laboratory tests were leucocytosis. Chest X-ray shows bronchopneumonia, pneumonia, and normal imaging. Obstetrics management was performed according to the condition of the mother and fetus, including vaginal delivery, cesarean section, and curettage. The treatment was using broad-spectrum antibiotics and antiviral. Complications in the fetus/infant were abortion, fetal distress, LBW, and asphyxia.Conclusion: Pregnant women with COVID-19 have mild or asymptomatic symptoms, hospitalized with complaints related to their pregnancy, and treatment according to the condition of the mother and fetus. There are no complications in the mother, while complications in the baby are not clear.Keywords: COVID-19, pregnant women, referral hospital. Abstrak Tujuan: Mengetahui gambaran klinis ibu hamil dengan COVID-19 yang masuk di rumah sakit rujukan COVID-19.Metode: Penelitian ini bersifat deskriptif yang dilakukan pada ibu hamil dengan COVID-19 yang dirawat di rumah sakit rujukan di Sulawesi Tenggara, yaitu RSUD Bau-Bau dan RSU Bahteramas di Kendari, pada bulan Mei sampai Juli 2020. Konfirmasi positif COVID-19 berdasarkan hasil pemeriksaan RT-PCR. Data berupa karakteristik, gambaran klinis, pemeriksaan penunjang, penatalaksanaan, dan luaran. Hasil: Terdapat 41 ibu hamil dengan COVID-19 dan tidak ada kasus kematian ibu. Usia ibu berkisar 19-39 tahun, tingkat pendidikan menengah, dan sebagai ibu rumah tangga. Sebagian besar kasus pada trimester-3, tidak tahu memiliki kontak erat, tidak memiliki komorbid, dan rujukan dari RS lain. Sebagian besar dirawat dengan keluhan terkait kehamilannya dan hanya 3 kasus dengan keluhan terkait COVID-19, yaitu demam dan batuk. Pemeriksaan laboratorium menunjukkan lekositosis. Gambaran foto toraks menunjukkan bronkopneumonia, pneumonia, dan normal. Tindakan obstetri dilakukan atas indikasi ibu dan janin, yaitu persalinan normal, seksio sesarea, dan kuretase. Terapi yang digunakan adalah antibiotic spectrum luas dan antivirus. Komplikasi pada janin/bayi berupa abortus, gawat janin, BBLR, dan asfiksia. Kesimpulan: Ibu hamil dengan COVID-19 memiliki gejala ringan atau asimtomatik, dirawat dengan keluhan terkait kehamilannya, dan dilakukan tindakan obstetri sesuai dengan indikasi ibu dan janin. Tidak ada komplikasi pada ibu, sedangkan komplikasi pada bayi belum jelas.Kata kunci: COVID-19, ibu hamil, rumah sakit rujukan